Appraisal of the Quality of Ground Waters in the Arid Zone of Rajasthan and Kutch - Gopal, Ram; Bhargava, T. N. (Defence Science Journal, 2014)
A survey and analyses of waters of arid zones of Western Rajasthan and Kutch have been presented. The data on physico-chemical characteristics of about 2000 ground water samples indicate that according to International Standards of drinking water as devised by WHO, 9 per cent waters in Rajasthan and 19 per cent in Kutch conform to permissible limits (TDS < 500 mg/l) and are suitable for drinking. Considering 2000 mg/l TDS, as maximum permissible level, 46 per cent of available waters in Western Rajasthan and 71 per cent in Kutch are potable. 38 and 57 per cent of waters have electrical conductivity less than 2250 micromhos/cm in Rajasthan and Kutch respectively. Salinity and toxicological studies of brackish waters and their remedial measures are also discussed. A tentative correlation between prevailing water-borne diseases, kidney diseases and fluorosis and dissolved solids in waters of Western Rajasthan has also been shown. The waters have been classified into various suitability classes depending upon their composition.